The information content of security prices - Beaver, William H.; Lambert, Richard A.; Ryan, Stephen G. (Journal of Accounting and Economics, 1987)
Beaver, Lambert and Morse (1980) employ a regression of percentage change in prices on percentage change in earnings in which data are grouped by the dependent variable. Reverse regression offers a more intuitive and direct way to assess the information content of security prices, the objective of Beaver et al. While grouping is asymptotically equivalent, reverse regression is a more efficient way of examining the incremental explanatory power of lagged values of percentage change in price with respect to accounting earnings.